Roles of mycorrhizal fungi on seed germination of two Chinese medicinal orchids: need or do not need a fungus? - Yang, Jing; Li, Neng-Qi; Gao, Jiang-Yun (Frontiers in Plant Science, 2024)
Generally, orchids highly depend on specific fungi for seed germination and subsequent seedling development in nature. For medicinal orchids, obtaining compatible fungi is prerequisite for imitation of wild cultivation and conservation. In this study, the two important traditional Chinese medicinal orchids, Pleione bulbocodioides and Bletilla striata, were studied to screen out effective fungi for seed germination and seedling development. P. bulbocodioides seeds germinated and formed protocorms in all fungal and control treatments, but seedlings only developed in fungal Serendipita officinale (SO) and S. indica (SI) treatments and nutrient-rich medium MS treatment. At 90 days after incubation, the percentages of seedlings were 34.83 ± 3.4% and 27.59 ± 3.5% in SO and SI treatments, which were significantly higher than the MS treatment (18.39 ± 2.0%; all P < 0.05). At this stage, most seedlings in SO and SI treatments bore two leaves (Stage 5), and pelotons inside the basal cells of seedlings were clearly observed. For B. striata, seeds germinated up to seedlings with or without fungus, but seedlings developed rapidly in SI treatment. At 90 days after incubation, the percentage of seedlings in SI treatment reached 77.90 ± 4.1%, but was significantly lower than the nutrient-poor medium OMA treatment (85.18 ± 3.7%; P < 0.01), however, the seedlings in SI treatment were stronger than the seedlings in OMA treatment.The results suggested that P. bulbocodioides rely on compatible fungi for seeds germinated up to seedlings, and fungus SO could effectively promote seed germination and support seedling development; while B. striata can germinate up to seedling without any fungus, but compatible fungus S. indica can greatly speed up seed germination and promote seedling development. We suggest that S. officinale and S. indica fungi can be used in conservation healthier 删除[朵]: 3 / 30 practices or imitation of wild cultivation of these two important medicinal orchids, respectively.